2012
DOI: 10.1152/jn.00057.2012
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoexcitation during chemoreflex active expiration is mediated byl-glutamate in the RVLM/Bötzinger complex of rats

Abstract: Moraes DJ, Zoccal DB, Machado BH. Sympathoexcitation during chemoreflex active expiration is mediated by L-glutamate in the RVLM/Bötzinger complex of rats. J Neurophysiol 108: 610 -623, 2012. First published April 25, 2012 doi:10.1152/jn.00057.2012The involvement of glutamatergic neurotransmission in the rostral ventrolateral medulla/Bötzinger/pre-Bötzinger complexes (RVLM/ BötC/pre-BötC) on the respiratory modulation of sympathoexcitatory response to peripheral chemoreflex activation (chemoreflex) was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
90
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(97 citation statements)
references
References 58 publications
7
90
0
Order By: Relevance
“…At 5% CO 2 , the inspiratory firing patterns of phrenic (PN), hypoglossal nerve (HN), and superior laryngeal nerve (SLN) were similar between rat strains and to those described previously 26,37,38 ( Figure S1A and Table S1 in the online-only Data Supplement). There was no rat strain difference in PN frequency or duration ( Figure S1A; Table S1).…”
Section: Differences In the Respiratory Pattern In Sh Relative To Wissupporting
confidence: 78%
See 3 more Smart Citations
“…At 5% CO 2 , the inspiratory firing patterns of phrenic (PN), hypoglossal nerve (HN), and superior laryngeal nerve (SLN) were similar between rat strains and to those described previously 26,37,38 ( Figure S1A and Table S1 in the online-only Data Supplement). There was no rat strain difference in PN frequency or duration ( Figure S1A; Table S1).…”
Section: Differences In the Respiratory Pattern In Sh Relative To Wissupporting
confidence: 78%
“…13,26,27,29 As with the thoracic sympathetic nerve, 13 we observed that all 3 sympathetic nerves recorded (ie, external and internal cervical sympathetic nerves [eCSN, iCSN], respectively, lumbar sympathetic) had augmented respiratory-modulation in SH rats (Figure S3A and S3B; Table S2). Specifically, SH rats exhibit increased inspiratory (iCSN, P<0.05 and eCSN, P<0.01; Figure S3B) and post-I-related sympathetic bursts (P<0.001; Figure S3B) and also an additional pre-I peak in the iCSN only ( Figure S3B) relative to that seen in Wistar rats (P<0.01; Figure S3A).…”
Section: Respiratory Modulation Of Cervical and Lumbar Sympathetic Nementioning
confidence: 68%
See 2 more Smart Citations
“…Since there are direct connections between ventrolateral respiratory neurons and presympathetic neurons in the rostral ventral lateral medulla (26), an increased respiratory drive may cause a leak to these presympathetic neurons, not only increasing the sympathetic outflow (26) but also changing their oscillatory profile. Effects of stimulation of chemoreceptors on sympathetic nerve activity reinforce our hypothesis (27). We cannot discard a possible influence of peripheral stretching pulmonary mechanoreceptors, which via vagal afferent neurons can affect the presympathetic neurons in the medulla (18).…”
Section: Discussionsupporting
confidence: 62%